Distinct physiological and transcriptional responses of leaves of paper mulberry (Broussonetia kazinoki × B. papyrifera) under different nitrogen supply levels. (23rd March 2020) - Ni, Jianwei; Su, Shang; Li, Hui; Geng, Yonghang; Zhou, Houjun; Feng, Yanzhi; Xu, Xinqiao
Abstract: Paper mulberry, a vigorous pioneer species used for ecological reclamation and a high-protein forage plant for economic development, has been widely planted in China. To further develop its potential value, it is necessary to explore the regulatory mechanism of nitrogen metabolism for rational nitrogen utilization. In this study, we investigated the morphology, physiology and transcriptome of a paper mulberry hybrid ( Broussonetia kazinoki  ×  B. papyrifera ) in response to different nitrogen concentrations. Moderate nitrogen promoted plant growth and biomass accumulation. Photosynthetic characteristics, concentration of nitrogenous compounds and activities of enzymes were stimulated under nitrogen treatment. However, these enhancements were slightly or severely inhibited under excessive nitrogen supply. Nitrite reductase and glutamate synthase were more sensitive than nitrate reductase and glutamine synthetase and more likely to be inhibited under high nitrogen concentrations. Transcriptome analysis of the leaf transcriptome identified 161, 961 unigenes. The differentially expressed genes associated with metabolism of nitrogen, alanine, aspartate, glutamate and glycerophospholipid showed high transcript abundances after nitrogen application, whereas those associated with glycerophospholipid, glycerolipid, amino sugar and nucleotide sugar metabolism were down-regulated. Combined with weighted gene coexpression network analysis, we uncovered 16 modules according to similarity in expression patterns. Asparagine synthetase and inorganic pyrophosphatase were considered two hub genes in two modules, which were associated with nitrogen metabolism and phosphorus metabolism, respectively. The expression characteristics of these genes may explain the regulation of morphological, physiological and other related metabolic strategies harmoniously. This multifaceted study provides valuable insights to further understand the mechanism of nitrogen metabolism and to guide utilization of paper mulberry.